Association between bedtime and female infertility: a secondary analysis from a cross-sectional study - Zhang, Hanzhi; Zhang, Jun; Chen, Wenxiu; Liu, Hongyu; Chen, Jingfei; Chen, Jianlin (Frontiers in Endocrinology, 2024)
Objective: To evaluate the association between bedtime and infertility and to identify the optimal bedtime for women of reproductive age.We conducted a cross-sectional study using data from 3,903 female participants in the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2020. The effect of bedtime on female infertility was assessed using the binary logistic regression in different models, including crude model and adjusted models. To identify the non-linear correlation between bedtime and infertility, generalized additive models (GAM) were utilized. Subgroup analyses were conducted by age, body mass index (BMI), waist circumference, physical activity total time, marital status, smoking status, drinking status and sleep duration.Results: After adjusting for potential confounders (age, race, sleep duration, waist circumference, marital status, education, BMI, smoking status, drinking status and physical activity total time), a non-linear relationship was observed between bedtime and infertility, with the inflection point at 22:45. To the left side of the inflection point, no significant association was detected.However, to the right of it, bedtime was positively related to the infertility (OR: 1.22; 95% CI: 1. to 1.39; P = 0.0049). Subgroup analyses showed that late sleepers with higher BMI were more prone